Hyaluronic acid nanoparticles as nanomedicine for treatment of inflammatory diseases - Rao, N. Vijayakameswara; Rho, Jun Gi; Um, Wooram; Ek, Pramod Kumar; Nguyen, Van Quy; Oh, Byeong Hoon; Kim, Wook; Park, Jae Hyung (Pharmaceutics, 2020)
Owing to their unique biological functions, hyaluronic acid (HA) and its derivatives have been explored extensively for biomedical applications such as tissue engineering, drug delivery, and molecular imaging. In particular, self-assembled HA nanoparticles (HA-NPs) have been used widely as target-specific and long-acting nanocarriers for the delivery of a wide range of therapeutic or diagnostic agents. Recently, it has been demonstrated that empty HA-NPs without bearing any therapeutic agent can be used therapeutically for the treatment of inflammatory diseases via modulating inflammatory responses. In this review, we aim to provide an overview of the significant achievements in this field and highlight the potential of HA-NPs for the treatment of inflammatory diseases.
Keywords: Atherosclerosis; Drug conjugates; Hyaluronic acid; Inflammatory diseases; Polymeric nanoparticles; Targeted-therapy; Tumor-targeting; Type 2 diabetes